Knowing women : same-sex intimacy, gender, and identity in postcolonial Ghana - Dankwa, Serena Owusua, 1975- (New York : Cambridge University Press, 2021)
"Knowing Women is an ethnography on friendship, same-sex desire, and intimacy among urban, working-class women in southern Ghana who engage in erotic relationships with each other. The intersectional analysis of these women's life narratives and world views situates them in relation to contemporary political, economic, and social developments affecting Ghana and other African societies in a postcolonial world. Prominent among these are the anti-gay policies and rhetoric and the pro-gay activism of local and international LGBTIQ advocacy organizations. Paying close attention to the women's own practices of self-reference, S. O. Dankwa refers to them as "knowing women" in a way that both distinguishes them from, and relates them to such categories as lesbian or supi a Ghanaian term for female friend(ship). In so doing it critically refutes both the anti-gay claim that homosexuality is "un-African" and the universalizing claim that queer identity categories exist in and can be translated between all languages and cultures. The book contributes to the burgeoning field of global queer studies in which both women and Africa have been largely underrepresented. In addition to engaging feminist, queer, Africanist and postcolonial theories of gender and sexuality, it responds to anthropological theories of kinship and gift-exchange"--
Includes bibliographical references and index.
Keywords: Lesbianism -- Ghana -- History; Lesbians -- Ghana -- Social life and customs; Interpersonal relations -- Ghana; Gender identity -- Ghana